Optimal operation mode of wind turbines in distribution grid to minimize energy loss considering power generation probability - Chung, Phan Dinh; An, Luu Ngoc; Hieu, Trinh Trung (IAES Indonesian Section, 2023)
This research considers a distribution grid where wind turbines were connected. The aim of this reasearch is to determine the optimal operation mode and setting parameter of wind turbines to minimize the energy loss of this distribution grid. To obtain the above purpose, we proposed an algorithm based on PSO algorithm. The suggested algorithm was coded in MATLAB and it was verified via a sample distribution grid. Results indicated the optimal operation mode and setting data in which the energy loss in the tested grid is minimal. Moreover, this research also compared the testing results with three cases of the generation at wind turbine node including average power, rated power and power probability distribution. Comparing results indicated that we cannot use average power generation or rated power of wind turbine to determine the optimal operation mode and setting data of wind turbines instead of we use the power distribution probability